The Correlation of Emotional Quotient (EQ) and Completeness of Drawing Tools with Student Motivation on Mechanical Engineering Drawings Study at Vocational High School: Hubungan Emotional Quotient (EQ) dan Kelengkapan Alat Gambar dengan Motivasi Belajar Siswa Pada Pembelajaran Menggambar Teknik Mesin di SMK - Rahmat, Muhammad Hudan (LPPM Institut Studi Islam Sunan Doe, 2023)
The purpose of this research is to examine the relationship between emotional quotient and completeness of drawing tools with learning motivation . This research is a correlational research. Based on the results of the study it was found that the majority of students (88%) had fairly high EQ scores, the majority of students (63%) had fairly complete drawing tools and the majority of students (54%) had high learning motivation. This study uses hypothesis testing which is tested by linear regression analysis. The results of the study show that (1) partially EQ has a positive relationship with learning motivation, (2) partially the completeness of drawing tools does not have a positive relationship with learning motivation, and (3) EQ and the completeness of drawing tools simultaneously have a positive relationship positive with student learning motivation. This shows that the higher the level of EQ and the completeness of the drawing tools owned by the students, the higher the student's learning motivation.